Contemporary Issues in Arbitration Agreements: Sharia Public Order and Civil Law Perspectives - Ghazi Ayed Alghathian; Mohammad Saleh Alqudah; Adel Salem Allouzi; Mashal Mufleh Jarrah (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This study examines contemporary issues concerning the law applicable to arbitration agreements in multinational corporate contracts and evaluates their compatibility with Sharia public order across five jurisdictions: France, Egypt, Jordan, Saudi Arabia, and the United Arab Emirates. Against the backdrop of evolving international arbitration practice, the study employs a doctrinal comparative legal methodology, supplemented by an illustrative analysis of 50 arbitration clauses from multinational corporate contracts, to assess contemporary drafting practices. The research analyzes three core doctrines of international arbitration law: separability of the arbitration agreement, extension of arbitration clauses to non-signatory group companies, and party autonomy in the choice of applicable law. The findings demonstrate that the separability doctrine is generally compatible with Sharia under the maxim al-‘ibrah bi al-maqāṣid wa al-ma‘ānī lā bi al-alfāẓ wa al-mabānī (substance over form), except where the main contract is void ab initio for violating a definitive (qaṭ‘ī) prohibition such as ribā or maysir. The study further finds that extension of arbitration agreements to non-signatories is permissible only upon clear evidence of fraud, active participation, or explicit or implied consent, while mere economic unity is insufficient under Sharia principles of contractual privity. In relation to party autonomy, the study concludes that parties may freely choose the governing law of the arbitration agreement provided that the chosen law does not contravene definitive Sharia prohibitions. The article proposes a reconciled framework based on a cumulative method that preserves party autonomy while requiring compliance with definitive Sharia norms forming part of public order in certain Arab jurisdictions. The study's academic contribution lies in integrating the doctrines of separability, non-signatory extension, and applicable law within a contemporary Sharia-based comparative framework. The findings offer practical guidance for cross-border commercial arbitration.